Daniel Deronda - Eliot, George, 1819-1880.; Cave, Terence (New York : Penguin Books, 1995)
Daniel, the adopted son of an English aristocrat, meets Mordecai, an ailing Jewish philosopher and his sister, Mirah, and begins to discover the secrets behind his own parentage.
First published 1876.
Includes bibliographical references (p. xxxvi-[xxxix]).
Adult
Keywords: Jews -- England -- Fiction; Zionists -- Fiction; Didactic fiction; Jews -- England -- Fiction; Zionists -- Fiction; England -- Fiction; England -- Fiction; Didactic fiction; Jewish fiction